CP-138 Successful off-label use of eltrompobag in pregnant woman with congenital thrombopenia. (24th March 2015) - Raymond, J; Descout, J; Aouba, A; Barbault-Foucher, S; Rieutord, A; Decottignies, A
Abstract : Background: Congenital thrombopenia is a rare disease. We report the case of a pregnant 25-year-old woman, suffering from a new form of severe congenital thrombopenia due to an autosomal recessive mutation in the PRKACG gene, found in 2014. The patient was advised not to plan such a high-risk pregnancy. A medical termination of pregnancy was rejected by the couple. Purpose: To report the off-label use of eltrombopag in a pregnant woman with congenital thrombopenia, allowing reaching a suitable platelet count for a safe delivery (vaginal birth: 30–50 G/L, caesarean: 50 G/L), scheduled at 35–37 weeks of amenorrhea (WA). Material and methods: Several off-label drugs were successively tested: intravenous immunoglobulin G (1 g/kg/day), and two thrombopoietin receptor agonists, romiplostim by the subcutaneous route (250 µg/week) and eltrombopag by oral route (50 to 125 mg daily). A multidisciplinary committee including haematologists, internists, obstetricians, pharmacists and pharmacologists from the Centre for Teratogenic Agents took the decision based on a risk-benefit approach. Twice-monthly platelet counts were performed and the dose was adjusted accordingly. Results: Intravenous immunoglobulin G showed an initial efficiency, raising the platelet count up to 115 G/L, but a relapse was observed after 1 month. This treatment was replaced by romiplostim, 6 months before pregnancy. Romiplostim stabilised the platelet count (275 G/L) until 6 WA and then lost progressively its effectiveness. The change to eltrombopag occurred at 20 WA. Platelet count increased up to 335 G/L at 24 WA and decreased gradually while keeping enough platelets until delivery. The patient gave birth by caesarean at 35 WA and 2 days, without haemorrhagic complications and platelet count was 80 G/L. The newborn was not affected by the disease. Conclusion: Eltrombopag was the most effective treatment in the management of this patient's thrombopenia and it enabled a high-risk pregnancy to achieve a successful outcome. References and/or Acknowledgements: No conflict of interest.